Le père Zeno Saltini et l’éducation du peuple à Nomadelfia: révolution et tradition d’un modèle de vie communautaire - Bandini, Gianfranco (Studi sulla Formazione/Open Journal of Education, 2014)
The work of Don Zeno Saltini (1900-1981) is unique and fascinating and has endured the test of time. He was in fact a great (albeit solitary) innovator who, during the time of conflict, strongly contested the idea that orphaned children should be sent to institutions and colleges. He helped develop the concept of forming a community of families prepared to take on single children, offering them a whole “educating community” (Nomadelfia, founded in 1948). In 1968 the community obtained special permission from the Ministry of Public Education to create an experimental school run entirely by parents. Popular education is intended as a special, original form of acceptance: the people in question are those who choose a communal way of life involving no consumerism and no need for money or private property, and essentially based on fraternity.